1992
DOI: 10.1210/mend.6.6.1379674
|View full text |Cite
|
Sign up to set email alerts
|

A single gene encodes the beta-subunits of equine luteinizing hormone and chorionic gonadotropin.

Abstract: Equine (e) CG and LH beta-subunits have identical amino acid sequences, including an extended carboxyl-terminal peptide (CTP). This suggests that unlike the corresponding human genes, the beta-subunits of eCG and eLH may be encoded by a single gene and share a common proximal promotor region. To explore this, we isolated and characterized the eLH/CG beta gene(s). Data from Southern analyses suggest that the eCG beta and eLH beta subunits are products of the same single copy gene (eLH/CG beta). Overlapping frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…1). In contrast to humans, no gene duplication occurred in the horse; the LH␤ gene lacking the CTP does not exist in equids, and the developmental pathway of the eLH/CG␤ CTP-bearing gene was proposed, based on sequence alignment with the LH␤ DNA of humans and cattle (7,10). The analyses showed that in humans and horses, frameshift deletion in the region of codons 112-115 of the ancestral LH␤ gene (deletion of one nucleotide in codon 114 and 10 bp subsequent to codon 111 in primates and equids, respectively) accounted for extension of the reading frame (4, 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In contrast to humans, no gene duplication occurred in the horse; the LH␤ gene lacking the CTP does not exist in equids, and the developmental pathway of the eLH/CG␤ CTP-bearing gene was proposed, based on sequence alignment with the LH␤ DNA of humans and cattle (7,10). The analyses showed that in humans and horses, frameshift deletion in the region of codons 112-115 of the ancestral LH␤ gene (deletion of one nucleotide in codon 114 and 10 bp subsequent to codon 111 in primates and equids, respectively) accounted for extension of the reading frame (4, 7).…”
Section: Resultsmentioning
confidence: 99%
“…3). Because the 3Ј region of the equine LH/CG␤ and bovine LH␤ genes was similar, we chose a strategy that mimicked the proposed developmental paradigm of the LH/ CG␤ gene subunit of the horse and donkey (7,10). The bovine LH␤ cDNA was modified by eliminating 10 bp in the 112-115 codons to shift the reading frame.…”
Section: Resultsmentioning
confidence: 99%
“…EMSA was performed using in vitro translated SF-1 and the 3ЈGSE oligonucleotide probe with an increasing molar excess of unlabeled 3ЈGSE or 5ЈGSE oligonucleotides (38), and human (39) are aligned with the core SF-1 binding site (GSE sequence) as defined in the human glycoprotein ␣-subunit and with the cognate Egr-1 site (1, 31). Nucleotide numbers are relative to the transcriptional start site of the rat sequence as defined by Jameson et.…”
Section: Sf-1 Binds Specifically To the Putative 3јgsementioning
confidence: 99%
“…As a heterodimer, it is composed of two subunits, an alpha (CGα), and a beta (CGβ), both are encoded by a single copy gene in both primates and equids (Pierce & Parsons, 1981). However, contrary to primates and hCG, the eCGβ and equine luteinizing hormone (eLH) are encoded by a single gene and also share a common proximal promoter region (Sherman et al, 1992). Both eCGα and eCGβ contain DNA regulatory elements that allow pituitary and placenta-specific expression (Talmadge et al, 1984a).…”
Section: Ecgmentioning
confidence: 99%
“…and LHβ polypeptides are almost identical and encoded by the same gene, indicating the coordinated regulation between the pituitary and placenta in horses (Talmadge & Fiddes, 1984b) (Bousfield et al, 1987). Also, it has been established that a single gene CGβ is evolved independently in primates and equids, thus using different mechanisms in their patterns of placenta-specific expression (Sherman et al, 1992).…”
Section: Ecg Productionmentioning
confidence: 99%